Study of the Relationship Between Environmental Perception and Environmental Impacts from the Mining Periquito in the Vila Amelia Neighborhood in Itabira/MG (Research, Society and Development, 2018)
This study aimed to investigate the perception of the residents of Vila Amélia neighborhood about the environmental impacts from the activity in the region as well as perform through an array of environmental impact assessment. The investigation was guided in the comparison between results obtained by applying of a survey with the residents of the neighborhood and the ones obtained in the application of Leopold matrix adapted. The results presented by Leopold matrix doesn’t faithfully represent the reality of the effects of the impacts experienced by residents of the neighborhood, since the comparison between the matrix and the survey results was convergence only for the biotic environment, having noticed divergence to the physical environment and socioeconomic , which puts in doubt the efficiency using only the matrix..